Combining polymer-bound catalyst with polymeric substrate for reproducible pH oscillations in palladium-catalysed oxidative carbonylation of alkynes. (December 2018) - Isakova, Anna; Parkes, George E.; Murdoch, Billy J.; Topham, Paul D.; Novakovic, Katarina
Graphical abstract: Highlights: pH oscillations in proline-chitosan-palladium catalyst, using phenylacetylene as a substrate. pH oscillations, using polymeric (pegylated dialkyne, PEGDA) substrate. Minimised leaching of palladium in proline-functionalised chitosan, compared to pristine. Reproducible pH oscillations of the original pattern generated by recycled catalyst. Abstract: Palladium-catalysed oxidative carbonylation (PCOC) of alkynes is a promising engine for building smart pulsatile polymeric systems, as it has demonstrated (in certain configurations) sustained regular oscillations in pH and redox potential for up to one month of monitoring in a batch reactor. Recent developments in polymer-supported palladium catalysts have demonstrated the full capacity of this reaction – in a macrogel that experienced oscillations in volume, while releasing a drug load. In this work, we demonstrate reproducible oscillations (more than 100 h duration) in a proline-functionalised chitosan-palladium system (Chi-Pro-Pd), using both small molecule (phenylacetylene) and polymeric (pegylated dialkyne) substrate, for the first time. Moreover, by functionalising chitosan with proline ligands, we dramatically reduced halide-mediated leaching of palladium, which readily occurred in non-functionalised chitosan-palladium catalysts (Chi-Pd). Oscillatory patterns for both systems confirm the need for fabricating functionalised chitosan supports to improve catalyst reusability and minimise loss of palladium.